An investigation into the benefits of integrating learners' prior everyday knowledge and experiences during teaching and learning of acids and bases in Grade 7: a case study - Kuhlane, Zukiswa (Rhodes University, Faculty of Education, Department of Education, 2012)
This study was conducted at a school designated as a higher primary school comprised of grade 0-9 learners (GET band) in Grahamstown in the Eastern Cape, South Africa. With the advent of the new curriculum in South Africa, we are also grappling with the implementation of the new curriculum at this school. This motivated me to investigate the benefits of eliciting and integrating learners' prior everyday knowledge and experiences during teaching and learning of acids and bases. Essentially, the study sought to gain insight into whether engaging learners during practical activities using easily accessible materials from their homes facilitated meaning-making of acids and bases. This study is located within an interpretive paradigm. Within this paradigm, a qualitative case study approach was conducted with the researcher's Grade 7 class. To gather data, document analysis, semi-structured interviews, questionnaires, lesson observations, stimulated recall discussions while watching the videotaped lessons as well as focus group interviews with learners were used. An inductive analysis to discover patterns and themes was applied during the data analysis process. The validation process was done through watching the videotaped lessons with the teachers who observed the lessons. Also, transcripts of the interviews and a summary of discussions were given back to the respondents to verify their responses and check for any misinterpretations. Rich data sets were analysed in relation to the research questions which were: How do Natural Sciences teachers elicit and integrate learners' prioreveryday knowledge and experiences to facilitate learning of scientific concepts of acids and bases in their classrooms? Does engaging learners in practical activities using everyday substances enhance their conceptual development and understanding of acids and bases? The findings from the study revealed that the use of learners' prior everyday knowledge and experiences during teaching and learning of acids and bases facilitated meaningful learning. Furthermore, linking learning to learners' everyday experiences enabled them to learn scientific concepts in a relaxed and non-threatening environment. It is thus recommended that teachers should be supported in their endeavours to incorporate learners' real life experiences during their teaching and learning repertoires. Notwithstanding, as much as there were benefits in this study there were, however, also some challenges that were encountered, such as language, which warrants further research.
Keywords: Science -- Study and teaching (Primary) -- Research -- South Africa; Prior learning -- South Africa; Limited English-proficient students -- Education (Primary) -- South Africa; Teaching -- Aids and devices -- Research